PENGARUH PENERAPAN STRATEGI AKTIF TIPE BENAR SALAH BERANTAI TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMP MUHAMMADIYAH 6 PADANG - Sari, Desi Ristia (STKIP PGRI Sumbar, 2014)
This research is motivated by low yields studying biology students in SMP Muhammadiyah 6 Padang. It is caused by a number of factors including the learning process in schools tend to be dominated by the teacher. In the learning process of students just listen and record what the teacher, so that students are less active in learning. One way to improve learning outcomes is to use True Type Active Implementation Strategy Against One Chain Biology Learning Outcomes Seventh Grade Students of SMP Muhammadiyah 6 Padang. This study aimed to reveal the effect of applying an active strategy completely wrong type of chain to the learning outcomes of students of class VII Biology SMP Muhammadiyah 6 Padang. This research is an experimental design using a randomized control group posttest-only design. The population in this study were all seventh grade students of SMP Muhammadiyah 6 Padang 2013-2014 academic year consists of 6 classes. Sampling using purposive sampling technique, in order to obtain two classes of samples with the draw of the obtained class as a class experiment VII1 and VII2 class as the control class. Analysis using t-test with a significance level of 0.05 corelation. The results of the analysis of data obtained t 3:00 while ttable 1.66. This means t count> t table, so the hypothesis is accepted. So it can be concluded that the application of an active strategy completely wrong type of chain can improve learning outcomes in biology students VII SMP Muhammadiyah 6 Padang.